PENGARUH REPUTASI KANTOR AKUNTAN PUBLIK (KAP), AUDIT TENURE, DAN DISCLOSURE TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN - Dian Elmawati; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2014)
This study aims to analyze and provide empirical evidence of the influence of audit firm reputation, audit tenure, and disclosure to the acceptance of going concern audit opinion. The proposed hypothesis are (1) Audit firm reputation negatively affects the acceptance of going concern audit opinion, (2) Audit tenure negatively affects the acceptance of going concern audit opinion, and (3) Disclosure positively affects the acceptance of going concern audit opinion. The data used is manufacturing companies listed on the Indonesia Stock Exchange (IDX) years 2007-2012. Samples were selected using purposive sampling method. Data were analyzed by logistic regression analysis with SPSS 21 application. Earlier researches in terms of going concern audit opinion have produced various results. The results from this research were as follows: (1) Audit firm reputation significantly affects the acceptance of going concern audit opinion, (2) Audit Tenure does not significantly affects the acceptance of going concern audit opinion, and (3) disclosure significantly affects the acceptance of going concern audit opinion.